PENGARUH PENERAPAN TEKNIK ICE BREAKING TERHADAP KONSENTRASI BELAJAR SOSIOLOGI DI KELAS X (FASE E) MA MUHAMMADIYAH TAMIANG UJUNG GADING PASAMAN BARAT - Fitra Hayati; Harisnawati; Faishal Yasin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the lack of concentration in students' learning in grade 10 (phase e) at MA Muhammadiyah Tamiang, Ujung Gading, West Pasaman. The purpose of this study was to examine the effect of the application of ice-breaking techniques on student concentration at MA Muhammadiyah Tamiang, Ujung Gading, West Pasaman.This research method was quantitative. The population in the study was all 66 grade 10 students, and the sample was 35 students from class X1, studying sociology at MA Muhammadiyah Tamiang, Ujung Gading, West Pasaman. Sampling was conducted using a total sampling technique. The instrument used for the study was a questionnaire, with a t-test used to test the hypothesis.The results showed that: There was a significant effect of the application of ice-breaking techniques on student concentration at MA Muhammadiyah Tamiang, Ujung Gading, West Pasaman. This can be seen from the results of the data analysis: t-test = 2.848 > t-table = 1.669. Therefore, it can be concluded that H1 is accepted, indicating that there is a significant effect of the application of the ice-breaking technique on the concentration of sociology learning in class X (phase e) of MA Muhammadiyah Tamiang, Ujung Gading, West Pasaman. Keywords: Ice-Breaking, Learning Concentration